DARI MEDAN PERTEMPURAN KEMBALI KE BARAK: KORPS WANITA ANGKATAN DARAT (KOWAD), 1960-1981 - Salebaran, Salebaran; Amini, Mutiah (Universitas Negeri Malang, 2021)
This article describes the assignment of the Army Women Corps (KOWAD) in the army during the Old Order and the New Order. by using a gender approach, as a way to identify and understand the placement of the Indonesian Army Women's Corps (KOWAD) in the Army during the Old and New Order periods. The conclusions of this paper are; First, during the Old Order era, the army provided room for assignment to the KOWAD Army Women Corps, apart from carrying out basic administrative tasks, they were also assigned to the combat sector. Meanwhile, during the New Order era, the army provided space for the assignment of the female army corps to certain tasks that were by the nature and nature of Indonesian women and carried out control of assignments following the manual for the Indonesian Army Corps for Women (KOWAD) Number SKEP / 754 / IX / 1974 as a guideline in carrying out all basic activities and duties of the Army. Second; The Army Women Corps (KOWAD) in carrying out the main duties of the Army has obstacles, namely; the domestication of the Indonesian Army Women's Corps (KOWAD) in the Army; as well as a dual role for the Indonesian Army Women's Corps (KOWAD). Artikel ini menjelaskan tentang penugasan Korps Wanita Angkatan Darat (KOWAD) dalam Angkatan Darat pada masa Orde Lama dan Orde Baru. Penelitian menggunakan pendekatan gender, sebagai salah satu cara untuk mengetahui dan memahami penempatan Korps Wanita Angkatan Darat (KOWAD) dalam Angkatan Darat pada pada masa Orde Lama dan Orde Baru. Adapun kesimpulan dari tulisan ini yakni; Pertama, pada masa Orde Lama, Angkatan Darat memberikan ruang penugasan terhadap Korps Wanita Angkatan Darat KOWAD selain menjalankan tugas pokok yang bersifat administratif juga ditugaskan dalam bidang tempur. Sedangkan masa Orde Baru, angkatan darat memberikan ruang penugasan korps wanita angkatan darat pada tugas-tugas tertentu yang sesuai dengan sifat dan kodrat wanita Indonesia serta melakukan pengontrolan penugasan sesuai dengan buku petunjuk Korps Wanita Angakatan Darat (KOWAD) Nomor SKEP/754/IX/1974 sebagai pedoman dalam menjalankan seluruh kegiatan dan tugas pokok Angkatan Darat. Kedua; Korps Wanita Angkatan Darat (KOWAD)dalam menjalankan tugas pokok Angkatan Darat memiliki hambatan yakni; adanya domestiifikasi Korps Wanita Angkatan Darat (KOWAD) dalam Angkatan Darat; serta peran ganda untuk Korps Wanita Angkatan Darat (KOWAD).